HBAR entropy of infalling atoms into a GUP-corrected Schwarzschild black hole and equivalence principle - Övgün, Ali; Pantig, Reggie C. (Elsevier, 2026)
In this work, we have investigated the phenomenon of acceleration radiation exhibited by a two-level atom freely falling into a Generalized Uncertainty Principle (GUP)-corrected Schwarzschild black hole. We derive analytic expressions for the atom's excitation probability with simultaneous emission of a scalar quantum and observe that it satisfies the Einstein equivalence principle when compared to the excitation probability induced by a uniformly accelerating mirror, motivated by studies [10.1103/PhysRevLett.121.071301] and [10.1073/pnas.1807703115]. Adopting an open-quantum-system framework, we then compute the horizon-brightened acceleration radiation (HBAR) entropy for the GUP-corrected spacetime and find that it reproduces the Bekenstein-Hawking entropy law, with corrections characteristic of GUP effects. These results underline the robustness of thermal radiation processes near horizons and the universality of entropy corrections in quantum-improved black hole spacetimes.
Keywords: Hawking radiation; Generalized uncertainty principle; Accelerating mirror; Black hole entropy